Unilateral conditioning contractions enhance power output in elite short track speed skaters - Gimenez, P.; Chicoine, E.; Amarantini, D.; Dal Maso, F.; Tremblay, J. (2018)
The objective of the present study was to assess the effect of unilateral lower-body-conditioning muscle contractions during multiple sets of fatiguing repeated jumps in elite athletes. Five elite short-track speed-skating athletes performed 9 sets of 6 maximal consecutive jumps on 2 separate occasions: with (COND) and without (CTRL) preliminary voluntary conditioning contractions (CC) 5 min before the beginning of the sets. The CC consisted of 2 consecutive 3 s maximal unilateral isometric squats against a fixed bar, resulting in a 6 s overall isometric contraction per leg. For each set, power output (PO) was measured using a linear position transducer and averaged over the 6 corresponding repeated jumps. The results showed that PO was significantly greater during the test in COND than in CTRL (p<0.01). PO significantly decreased with sets, by 19.4±4.7 and 15.2±7.6% (p<0.001) between the first and last set in COND and CTRL, respectively. A 2×3 s maximal unilateral isometric CC, performed 5?min before unloaded repeated jumps, significantly increased mean PO. These results suggest that unilateral conditioning contractions can enhance performance in subsequent bilateral repeated jumps.